A review of external assistance and aid effectiveness for maternal and child health: Challenges and opportunities - Zulfiqar A. Bhutta; Samia Aleem (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper primarily focuses on how global funding has supported interventions that have proven to be successful in reducing maternal, newborn, and child mortality around the world. The growth rate of development assistance targeted towards these specific interventions has varied greatly over the past years, and we highlight the channels through which funds reach their target recipients. An important conclusion to note is the need for donors to align their programmes with government-defined priorities in order to ensure the achievement of national development objectives, long-term sustainability, and success.
Keywords: F35; I15; I18; J13; 330; foreign aid; aid effectiveness; maternal; newborn and child health interventions